Patient satisfaction with doctor-patient interaction and its association with modifiable cardiovascular risk factors among moderately-high risk patients in primary healthcare - Mohd Noor, Norhayati; Abd Aziz, Masseni; Ishak, Azlina (PeerJ, 2017)
Background. The outcomes of the physician-patient discussion intervene in the satisfaction of cardiovascular disease risk patients. Adherence to treatment, provision of continuous care, clinical management of the illness and patients' adjustment are influenced by satisfaction with physician-patient interaction. This study aims to determine patient satisfaction with doctor-patient interactions and, over six months after following prevention counselling, its associations with modifiable cardiovascular risk factors amongst moderately-high risk patients in a primary healthcare clinic in Kelantan, Malaysia. Methods. A prospective survey was conducted amongst patients with moderately-high cardiovascular risk. A total of 104 moderately-high risk patients were recruited and underwent structured prevention counselling based on the World Health Organization guideline, and their satisfaction with the doctor-patient interaction was assessed using `Skala Kepuasan Interaksi Perubatan-11,' the Malay version of the Medical Interview Satisfaction Scale-21. Systolic blood pressure, total cholesterol and high-density lipoprotein cholesterol were measured at baseline and at a follow-up visit at six months. Descriptive analysis, paired t test and linear regression analyses were performed. Results. A total of 102 patients responded, giving a response rate of 98.1%. At baseline, 76.5% of the respondents were satisfied with the relation with their doctor, with the favourable domain of distress relief (85.3%) and rapport/confidence (91.2%). The unfavourable domain was interaction outcome, with satisfaction in only 67.6% of the respondents. Between the two visits, changes had occurred in total cholesterol (P D0:022) and in systolic blood pressure (P <0:001). Six months after the initial visits, no relationship existed between patient satisfaction scores and changes in modifiable cardiovascular risks. Discussion. The `Skala Kepuasan Interaksi Perubatan-11' which represents a component of the interpersonal doctor-patient relationship can be used to assess improvements of the medical skills and in medical training to enhance the quality of therapeutic communication.